JENIS DAN POLA PENYEDERHANAAN BUNYI DALAM BAHASA BALI - Dewa Ayu Dyah Pertiwi Putri; Agus Darma Yoga Pratama (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2026)
This study aims to find out the types and patterns of sound simplification in Balinese. The study uses a qualitative approach with an observation method and is supplemented by note-taking techniques. The data in this study are sounds in Balinese words that have undergone sound simplification. The data are sourced from 10 informants who are native Balinese and actively use Balinese in their daily lives. The results of the study indicate that the types of sound simplification found in Balinese are 1) Apheresis, 2) Syncope, 3) Apocope, and 4) Sound Shift, both vertically and horizontally; while the patterns of sound simplification are 1) equalizing the quality of vowel clusters, 2) relaxing or lowering the quality of adjacent sounds, and 3) eliminating certain syllables partially or completely.